Building an Affordances Map With Interactive Perception - Le Goff, Léni K.; Yaakoubi, Oussama; Coninx, Alexandre; Doncieux, Stéphane (Frontiers in Neurorobotics, 2022)
Robots need to understand their environment to perform their task. If it is possible to pre-program a visual scene analysis process in closed environments, robots operating in an open environment would benefit from the ability to learn it through their interaction with their environment. This ability furthermore opens the way to the acquisition of affordances maps in which the action capabilities of the robot structure its visual scene understanding. We propose an approach to build such affordances maps by relying on an interactive perception approach and an online classification for a real robot equiped with two arms with 7 degrees of freedom. Our system is modular and permits to learn maps from different skills. In the proposed formalization of affordances, actions and effects are related to visual features, not objects, thus our approach does not need a prior definition of the concept of object. We have tested the approach on three action primitives and on a real PR2 robot.